Rapid preparation of expandable graphite by using ultrasonic irradiation technique: article - Mohd Hisham, Nurhidayah; Othman, Nur Hidayati (2017)
Expandable graphite was prepared by using ultrasonic irradiation technique without causing damage to the graphite itself after being modified. From this preparation of expandable graphite, the mechanism of intercalation and exfoliation was studied to determine how graphite was synthesized from flake to expandable graphite. A mixture of flake graphite and ultrasonic solvent was prepared and undergo sonication inside an ultrasonic bath. In this work XX types of solvents were used. The maximum ultrasonic time was kept for 4 hours. The expansion of the graphite was observed and the volume of expandable graphite was obtained during washing process. The expandable graphite was then dried inside the oven at the temperature of 60°C. X-ray diffraction analysis was then used to determine the crystallographic structure of expandable graphite. Besides that, Fourier Transform Infrared was also used to determine the existence of any functional group in expandable graphite prepared. It was found that, nitric acid was the best solvent to be used as intercalant with 3 hours sonication time and high ultrasonic power. The crystalline structure of graphite was observed to remain the same after being expanded using ultrasonic method. Therefore, it is considered as an excellent graphite modification method in producing huge amount of high quality graphene instead of using original flake graphite.